Manganese-based material as well as preparation method and application thereof

By introducing a dispersed Mn vacancy structure into the transition metal layer of the manganese-based material, the redox activity of lattice oxygen is activated, and the low efficiency and attenuation problems of existing lithium-rich manganese-based positive electrode materials in lithium-ion batteries are solved, and high capacity, stability and rate performance are improved.

CN119725515AActive Publication Date: 2025-03-28SUN YAT SEN UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411922496.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials have problems of low Coulomb efficiency, serious capacity and voltage attenuation for the first time, and poor rate performance.

Method used

By introducing a dispersed Mn vacancy structure into the transition metal layer of the manganese-based material, the redox activity of lattice oxygen is activated, the migration of Mn in the layer and the formation of oxygen molecules is inhibited, thereby improving the redox reversibility of the material.

Benefits of technology

It has achieved the improvement of the actual working capacity, cycle stability and cycle life of lithium-ion batteries, alleviated the voltage attenuation problem, and improved the rate performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725515A_ABST
    Figure CN119725515A_ABST
Patent Text Reader

Abstract

The invention discloses a manganese-based material as well as a preparation method and application thereof. The crystal structure of the manganese-based material comprises an alkali metal layer, an O element and a transition metal layer, the alkali metal layer comprises Li element; the transition metal layer comprises an Mn element and an Mn vacancy, or the Mn element, the Mn vacancy and a Li element. In the manganese-based material with the specific structure, the unique Mn vacancy in the transition metal layer can activate the oxidation-reduction activity of oxygen anions, extra capacity is provided in the charge-discharge process, and the existing crystal structure configuration of the material is enriched; furthermore, structure reverse design and in-situ lithium supplementation are carried out according to the characteristic that the material is lack of lithium, application of the structure in the aspect of the lithium ion battery is optimized, rearrangement of the Mn vacancy superstructure in the transition metal layer can be caused by addition of additional lithium atoms, and the lithium ion battery performance is improved. The more dispersed vacancy configuration can better inhibit irreversible loss of lattice oxygen and structural phase change and capacity loss caused by intra-layer / inter-layer migration of manganese.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage, and in particular relates to a manganese-based material and a preparation method and application thereof. Background Art

[0002] With the booming development of portable mobile electronic devices, electric vehicles and large-scale energy storage grids, people's demand for high-performance lithium-ion batteries continues to expand. However, the actual capacity of commercial cathode materials has greatly restricted the further improvement of the energy density of lithium-ion batteries, and it is urgent to develop new cathode materials with higher capacity. O3 phase lithium-rich manganese-based cathode materials have a unique "Li-O-Li" configuration, which can activate lattice oxygen to participate in redox reactions. This kind of anion / cation synergistic charge compensation mechanism makes this type of material show ultra-high specific capacity, which is an ideal next-generation cathode alternative material. However, uncontrollable oxygen loss triggers the intralayer and interlayer migration of Mn ions, and the accumulation of oxygen vacancies leaves nano-voids inside the material, which makes the lithium-rich manganese-based cathode materials have low first coulombic efficiency, severe capacity and voltage decay in the actual application of lithium-ion batteries. The slow reaction kinetics of Mn make the rate performance poor, which seriously hinders its commercial application.

[0003] At present, there are many modification methods such as doping and coating of basic materials to solve the above problems. However, the introduction of impurity atoms or coating layers cannot fundamentally solve the intrinsic problems of materials. Sodium-ion batteries often exhibit similar electrochemical behaviors to lithium-ion batteries. The same problem also exists in sodium-rich manganese-based cathode materials. The difference is that its structural diversity (P2 / P3 structure, vacancy / Li / other elements replacing TM) provides more options for solving the intrinsic problems of materials. For example, Na2Mn3O7 (Na 4 / 7 [□ 1 / 7 Mn 6 / 7 ]O2) In the sodium-based cathode oxide, 1 / 7 of the Mn in the transition metal layer is replaced by vacancies, forming a regular mesh vacancy structure. The presence of such dispersed Mn vacancies can activate lattice oxygen while improving its redox reversibility, and inhibit the intralayer migration of Mn and the formation of oxygen molecules. Direct structural design can fundamentally solve the problems existing in this type of material without introducing impurity atoms, effectively alleviate the problem of lattice oxygen release under high voltage, reduce the irreversible capacity loss in the first cycle, improve the long cycle life of the battery, and alleviate problems such as voltage decay. However, there is a lack of similar structural reports in lithium-based cathode oxide materials, and the traditional solid-phase sintering method is difficult to synthesize. Therefore, the development of a high-energy-density lithium-ion positive electrode material with a new structure and that can be prepared is still a topic worthy of study. Summary of the invention

[0004] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a manganese-based material, wherein the transition metal layer of the manganese-based material contains dispersed Mn vacancy structures, the presence of which can activate lattice oxygen while improving the redox reversibility of the material and inhibiting the intralayer migration of Mn and the formation of oxygen molecules.

[0005] A second object of the present invention is to provide a method for preparing the above-mentioned manganese-based material.

[0006] A third object of the present invention is to provide a positive electrode material.

[0007] A fourth object of the present invention is to provide a lithium ion battery.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] A first aspect of the present invention provides a manganese-based material, wherein the crystal structure of the manganese-based material comprises an alkali metal layer, an O element and a transition metal layer; the O element is located between the alkali metal layer and the transition metal layer, and is respectively combined with the alkali metal layer and the transition metal layer; the alkali metal layer comprises a Li element; the transition metal layer comprises a Mn element and a Mn vacancy, or a Mn element, a Mn vacancy and a Li element;

[0010] The molar ratio of the O element to the Li element in the alkali metal layer is 1:(0.2-0.4);

[0011] The molar ratio of the O element to the Mn element is 1:(0.3-0.6);

[0012] The molar ratio of the Mn vacancy to the Mn element is greater than 0 and less than or equal to 1 / 6;

[0013] The molar ratio of the Li element to the Mn element in the transition metal layer is 0 to 0.16.

[0014] The manganese-based material of the specific structure of the present invention contains a specific proportion of Mn vacancy structure. The presence of this special structure will change the Mn-O electronic coordination environment around the Mn vacancy, and the 2p orbital electrons of the lattice oxygen can interact more effectively with the conduction band electrons, providing a way for electron transfer for the activation of the lattice oxygen, participating in the charge compensation behavior in the lithium ion deintercalation process, and improving the actual working capacity of the lithium ion battery. The presence of the dispersed Mn vacancy structure increases the intralayer / interlayer migration barrier of Mn during the long cycle process, and when the adjacent lattice oxygen is oxidized to peroxide ions and wants to further oxidize and combine to form oxygen escape, it is inhibited, thereby improving the redox reversibility of lattice oxygen. The inhibition of Mn migration behavior improves the stability of the material structure, and solves the problem of capacity and voltage decay caused by phase structure transformation or layered structure collapse due to intralayer / interlayer migration of Mn in traditional anion redox lithium manganese-rich materials. While providing high charge and discharge capacity, the material improves the redox reversibility of oxygen anions, alleviates the collapse of the material structure caused by Mn migration, and improves cycle stability and cycle life.

[0015] In particular, when the molar ratio of Mn vacancies to Mn elements is 1:6, a mesh vacancy structure is formed. This structure is a superstructure existing in the transition metal layer synthesized by adjusting the Li / Mn stoichiometric ratio. As the proportion of Mn elements increases, the vacancy structure undergoes the following transformation: honeycomb → band → mesh structure.

[0016] In the present invention, when the molar ratio of the Li element to the Mn element in the transition metal layer is 0:1, it means that the transition metal layer is not doped with the Li element; and when the molar ratio of the Li element to the Mn element in the transition metal layer is greater than 0:1, it means that the transition metal layer is doped with the Li element, and the doped Li element will replace the Mn vacancies in the transition metal layer, thereby further reducing the proportion of Mn vacancies.

[0017] In some specific embodiments of the present invention, the crystal structure of the manganese-based material includes an O2 phase structure, an O3 phase structure or a combination thereof; further preferably, the manganese-based material is selected from the O3 phase structure.

[0018] The O3 phase is a face-centered cubic crystal structure with an ABCABC periodic stacking layer. "O (Octahedron) represents the octahedral coordination environment of the alkaline cation, which represents lithium in the present invention. The number "3" represents the number of TMO2 plates in a single unit cell (TM: transition metal element Mn). The lithium layer and transition metal layer of the O2 phase are stacked along the c-axis direction, and the stacking order is ABAB..., and the number of TMO2 plates in a single unit cell is 2.

[0019] In some specific embodiments of the present invention, the transition metal layer of the manganese-based material includes a Li-O-□ structure, a Li-O-Li structure or a combination thereof. "□" represents a Mn vacancy.

[0020] In the present invention, when the transition metal layer is not doped with Li element, oxygen is used as the central atom, which combines with Li of the alkali metal layer and the vacancies of the transition metal layer to form a special internal structure of Li-O-□; and when the transition metal layer is doped with Li element to replace some of the vacancies, an internal structure of Li-O-Li will appear.

[0021] Preferably, the transition metal layer includes Mn elements, Mn vacancies and Li elements; the molar ratio of Li elements to Mn elements in the transition metal layer is greater than 0 and less than or equal to 0.16; further preferably, it is (0.03-0.16):1; further preferably, it is (0.05-0.12):1; more preferably, it is (0.07-0.1):1.

[0022] When the transition metal layer is doped with Li, it is beneficial to improve the intrinsic lithium-deficient properties of the undoped Li material in the transition metal layer, partially occupy the Mn vacancies with Li, and can improve the charging capacity of the first cycle. The lithium in the transition metal layer does not participate in the lithium insertion and extraction behavior during the charging and discharging process, which can further improve the stability of the structure and the long cycle life of the material. Preferably, the molar ratio of the Mn vacancies to the Mn element is greater than 0 and less than 1 / 6; more preferably 0.03 to 0.1; non-limiting specific examples are 0.03, 0.05, 0.08 or 0.1.

[0023] As the proportion of Mn elements increases or the Li element occupies the transition metal layer, the content of Mn vacancy structure decreases, and the special structure formed has better electrochemical performance.

[0024] Preferably, the molar ratio of the O element to the Li element in the alkali metal layer is 1:(0.25-0.36); more preferably, it is 1:(0.27-0.34).

[0025] Preferably, the molar ratio of the O element to the Mn element is 1:(0.35-0.55); more preferably, it is 1:(0.4-0.5).

[0026] In some specific embodiments of the present invention, the structural formula of the manganese-based material is Li 0.64 [□ 0.14 Mn 0.86 ]O2、Li 0.57 [□ 0.14 Mn 0.86 ]O2、Li 0.64 [Li 0.11 □0.03 Mn 0.86 ]O2 or Li 0.64 [Li 0.09 □ 0.05 Mn 0.86 ]O2.

[0027] The second aspect of the present invention provides a method for preparing the manganese-based material described in the first aspect of the present invention, comprising the following steps: calcining a mixture containing sodium carbonate and manganese carbonate, or a mixture containing sodium carbonate, manganese carbonate and a first lithium source for a first time to obtain a precursor; then mixing the precursor with a second lithium source, and performing an ion exchange reaction through a second calcination to obtain the manganese-based material; the first lithium source and the second lithium source are the same or different.

[0028] In the preparation method of the present invention, a precursor material (such as Na2Mn3O7) with a Mn vacancy ordered structure, or a NaLiMnO (NLMO) precursor material doped with lithium sources is first prepared by a solid phase sintering method; then, an ion exchange method is used to replace the sodium ions in the precursor material with lithium ions through ion exchange to synthesize a manganese-based material with a specific structure.

[0029] Specifically, the present invention adopts ion exchange method, which can achieve the purpose of synthesizing the desired specific structure, and solves the problem that the traditional solid phase sintering method cannot prepare lithium ion Mn vacancy materials. From the perspective of material structure design, lithium ions can only accept octahedral structures, while sodium ions can adapt to prismatic and octahedral structures. When there is a vacancy structure in the transition metal layer, the lattice structure will be distorted, the material symmetry will be reduced, and the sodium ions with larger ionic radius can move relatively freely in the lattice during the sintering process. The larger ion diffusion characteristics and diffusion channels help to fill the position around the vacancy or adjust their own distribution, relieve the local structural stress caused by the formation of Mn vacancies, so that the material can still maintain a certain structural integrity in the case of Mn vacancies. Therefore, the mild preparation conditions of the ion exchange method reduce the occurrence of material side reactions, achieve the purpose of maintaining the structure of the sodium-based precursor and obtaining products with electrochemical activity. This is of great significance for the development of high-performance lithium-based positive electrode materials, especially for some lithium-based positive electrode materials with specific structures that are difficult to synthesize by traditional methods. In addition, the vacancy order of the precursor material can be adjusted by doping Li or Mn, and the requirements of different application scenarios of lithium-ion cathode materials can be met after ion exchange.

[0030] Preferably, the calcination temperature of the first calcination is 500-700°C; more preferably 550-650°C; further preferably 580-620°C.

[0031] Preferably, the holding time of the first calcination is 12 to 18 hours; more preferably, it is 14 to 16 hours.

[0032] Preferably, the calcination temperature of the second calcination is 200-300°C; more preferably, 250-290°C; and even more preferably, 270-280°C.

[0033] Preferably, the holding time of the second calcination is 2 to 10 hours; more preferably 4 to 8 hours; and even more preferably 5 to 7 hours.

[0034] Preferably, the first lithium source includes at least one of lithium carbonate, lithium sulfate, lithium chloride or lithium nitrate; further preferably, the first lithium source is selected from lithium carbonate.

[0035] Preferably, the second lithium source includes at least one of lithium carbonate, lithium sulfate, lithium chloride or lithium nitrate; further preferably, the second lithium source is selected from lithium chloride and lithium nitrate;

[0036] Among the second lithium sources used in the ion exchange preparation process, lithium chloride and lithium nitrate, which have lithium ion chemical activity and stable chemical properties, are selected as exchange lithium sources to obtain better energy efficiency and cost-effectiveness. These two lithium sources have a low minimum eutectic temperature (280°C), which can well ensure that the material undergoes sufficient ion exchange reaction without destroying the original structure of the material and avoiding unnecessary side reactions under such low temperature conditions. In addition, both lithium sources can be well dissolved in water, which is conducive to washing the excess lithium source from the material after ion exchange.

[0037] Preferably, in the second lithium source, the mass ratio of the lithium chloride to the lithium nitrate is 1:(7-8); more preferably 1:(7.2-7.5).

[0038] According to the binary phase diagram, when lithium chloride and lithium nitrate are at the lowest eutectic temperature, the mass ratio of the two phases is 12:88, so a lower ion exchange temperature can be obtained near this mass ratio.

[0039] Preferably, in the mixture containing sodium carbonate and manganese carbonate, the molar ratio of sodium carbonate to manganese carbonate is 1:(2-4); more preferably 1:(2.5-3.5); and even more preferably 1:(2.8-3.2).

[0040] Preferably, in the mixture containing sodium carbonate, manganese carbonate and the first lithium source, the molar ratio of sodium carbonate to manganese carbonate is 1:(2-4); more preferably 1:(2.5-3.5); and even more preferably 1:(2.8-3.2).

[0041] Preferably, in the mixture containing sodium carbonate, manganese carbonate and the first lithium source, the molar ratio of manganese in manganese carbonate to lithium in the first lithium source is (0.03-0.16):1; more preferably (0.05-0.12):1; and even more preferably (0.07-0.1):1.

[0042] The first calcination is performed using a mixture containing sodium carbonate, manganese carbonate and the first lithium source. The first lithium source is added as a lithium source during the preparation of the precursor to supplement lithium in situ, synthesize NaLiMnO material, and then perform ion exchange. The chemical formula of the precursor material obtained without adding the first lithium source is Na2Mn3O7, which can also be written as Na 0.57 [□ 0.14 Mn 0.86 ]O2, so there are 0.14 mol of Mn vacancies in the transition metal layer of 1 mol of the material. The present invention performs in-situ lithium replenishment by occupying these vacancies with lithium ions in different proportions. When the ratio of lithium atoms to manganese atoms doped in the transition metal layer is (0.03-0.16):1, it has a good lithium replenishment effect.

[0043] The third aspect of the present invention provides a positive electrode material, wherein the raw material for preparing the positive electrode material comprises the manganese-based material described in the first aspect of the present invention, or the manganese-based material prepared by the preparation method described in the second aspect of the present invention.

[0044] The fourth aspect of the present invention provides a lithium ion battery, comprising the positive electrode material described in the third aspect of the present invention.

[0045] The beneficial effects of the present invention are as follows: in the manganese-based material of the specific structure of the present invention, the unique Mn vacancies in the transition metal layer can activate the redox activity of oxygen anions, provide additional capacity during the charge and discharge process, and enrich the existing crystal structure configuration of this material; further, the structure is reversely designed according to the lithium deficiency characteristics of the material, lithium is supplemented in situ, and the application of the structure in lithium-ion batteries is optimized. The addition of additional lithium atoms will lead to the rearrangement of the Mn vacancy superstructure in the transition metal layer, and the more dispersed vacancy configuration can better inhibit the irreversible loss of lattice oxygen and the structural phase change and capacity loss caused by the migration within / between the manganese layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 The XRD patterns of the samples of Examples 1 to 3 of the present invention are shown in FIG.

[0047] Figure 2 2, 4 and 5 are XRD patterns of samples of Examples 2, 4 and 5 of the present invention.

[0048] Figure 3 4, 6 and 7 are XRD patterns of samples of Examples 4, 6 and 7 of the present invention.

[0049] Figure 4 The XRD patterns of the samples of Examples 8 to 11 and Example 4 of the present invention are shown in FIG.

[0050] Figure 5 These are SEM images of samples of Example 4 and Example 10 of the present invention.

[0051] Figure 6 This is the EDS element spectrum of the sample in Example 4 of the present invention.

[0052] Figure 7 This is the EDS element spectrum of the sample in Example 10 of the present invention.

[0053] Figure 8 Electrochemical performance test diagram of batteries assembled from samples of Example 4 and Example 10 of the present invention. DETAILED DESCRIPTION

[0054] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.

[0055] Example 1

[0056] A manganese-based material, the preparation method is as follows:

[0057] 1) Firstly, sodium carbonate and manganese carbonate powders were weighed in a molar ratio of 1:3 and put into a ball mill, and ball milled and mixed for 24 hours at a rotation speed of 400 rpm to obtain a mixture;

[0058] 2) The obtained mixture was spread in a square porcelain boat, placed in a tube furnace and oxygen was introduced, and heated to 450°C at a heating rate of 5°C / min and kept for 5 hours in a pure oxygen atmosphere at room temperature of 25°C, and then heated to 500°C at a heating rate of 3°C / min and kept for 12 hours, and then cooled naturally to room temperature while maintaining ventilation to obtain a Na2Mn3O7 precursor;

[0059] 3) Na2Mn3O7 precursor, lithium chloride and lithium nitrate were weighed in a molar ratio of 1:2.4:17.6 and ground in a mortar for 30 minutes to uniformly mix the materials, and the mixture was transferred to a nickel crucible and placed in a muffle furnace, and heated to 250°C at a heating rate of 4°C / min at room temperature in an air atmosphere, and then kept warm for 15 minutes, and then continued to heat to 280°C at a heating rate of 2°C / min and kept warm for 6 hours, and then naturally cooled to room temperature to obtain a calcined product;

[0060] 4) The calcined product was washed and filtered three times with deionized water and anhydrous ethanol respectively to remove excess lithium salt and sodium salt. The final clean material was transferred to a glass dish and dried in an oven for 24 hours to remove excess moisture to obtain Li2Mn3O7 material (LMO-500℃), which was finely ground and sealed for dry storage.

[0061] Example 2

[0062] A manganese-based material, the preparation method is as follows:

[0063] 1) Firstly, sodium carbonate and manganese carbonate powders were weighed in a molar ratio of 1:3 and put into a ball mill, and ball milled and mixed for 24 hours at a rotation speed of 400 rpm to obtain a mixture;

[0064] 2) The obtained mixture was spread in a square porcelain boat, placed in a tube furnace and oxygen was introduced, and heated to 450°C at a heating rate of 5°C / min and kept for 5 hours in a pure oxygen atmosphere and room temperature of 25°C, and then heated to 600°C at a heating rate of 3°C / min and kept for 12 hours, and then cooled naturally to room temperature while maintaining ventilation to obtain a Na2Mn3O7 precursor;

[0065] 3) Na2Mn3O7 precursor, lithium chloride and lithium nitrate were weighed in a molar ratio of 1:2.4:17.6 and ground in a mortar for 30 minutes to uniformly mix the materials, and the mixture was transferred to a nickel crucible and placed in a muffle furnace, and heated to 250°C at a heating rate of 4°C / min at room temperature in an air atmosphere, and then kept warm for 15 minutes, and then continued to heat to 280°C at a heating rate of 2°C / min and kept warm for 6 hours, and then naturally cooled to room temperature to obtain a calcined product;

[0066] 4) The calcined product was washed and filtered three times with deionized water and anhydrous ethanol respectively to remove excess lithium salt and sodium salt. The cleaned material was transferred to a glass dish and dried in an oven for 24 hours to remove excess moisture to obtain Li2Mn3O7 material (LMO-600℃), which was finely ground and sealed for dry storage.

[0067] Example 3

[0068] A manganese-based material, the preparation method is as follows:

[0069] 1) Firstly, sodium carbonate and manganese carbonate powders were weighed in a molar ratio of 1:3 and put into a ball mill, and ball milled and mixed for 24 hours at a rotation speed of 400 rpm to obtain a mixture;

[0070] 2) The obtained mixture was spread in a square porcelain boat, placed in a tube furnace and oxygen was introduced, and heated to 450°C at a heating rate of 5°C / min and kept for 5 h in a pure oxygen atmosphere at room temperature of 25°C, and then heated to 700°C at a heating rate of 3°C / min and kept for 12 h, and then cooled naturally to room temperature while maintaining ventilation to obtain a Na2Mn3O7 precursor;

[0071] 3) Na2Mn3O7 precursor, lithium chloride and lithium nitrate were weighed in a molar ratio of 1:2.4:17.6 and ground in a mortar for 30 minutes to uniformly mix the materials, and the mixture was transferred to a nickel crucible and placed in a muffle furnace, and heated to 250°C at a heating rate of 4°C / min at room temperature in an air atmosphere, and then kept warm for 15 minutes, and then continued to heat to 280°C at a heating rate of 2°C / min and kept warm for 6 hours, and then naturally cooled to room temperature to obtain a calcined product;

[0072] 4) The calcined product was washed and filtered three times with deionized water and anhydrous ethanol respectively to remove excess lithium salt and sodium salt. The cleaned material was transferred to a glass dish and dried in an oven for 24 hours to remove excess moisture to obtain Li2Mn3O7 material (LMO-700℃), which was finely ground and sealed for dry storage.

[0073] The difference between Examples 1 to 3 is that the precursor sintering temperatures are different, which are 500, 600, and 700°C, respectively. The prepared materials are confirmed by X-ray diffraction with a scanning range of 10 to 90°. The obtained XRD patterns are as follows: Figure 1 As shown, it can be seen that the material prepared at 500°C has poor crystallinity, and the material at 700°C is a mixed phase of O2 and O3, the structural symmetry is reduced, and the stability is not as good as the pure O3 phase cathode oxide material sintered at 600°C, so the sintering temperature of subsequent precursors is 600°C.

[0074] Example 4

[0075] A manganese-based material, the preparation method is as follows:

[0076] 1) Firstly, sodium carbonate and manganese carbonate powders were weighed in a molar ratio of 1:3 and put into a ball mill, and ball milled and mixed for 24 hours at a rotation speed of 400 rpm to obtain a mixture;

[0077] 2) The obtained mixture was spread flat in a square porcelain boat, placed in a tube furnace and oxygen was introduced, and heated to 450°C at a heating rate of 5°C / min and kept for 5 hours in a pure oxygen atmosphere and room temperature of 25°C, and then heated to 600°C at a heating rate of 3°C / min and kept for 15 hours, and then cooled naturally to room temperature while maintaining ventilation to obtain a Na2Mn3O7 precursor;

[0078] 3) Na2Mn3O7 precursor, lithium chloride and lithium nitrate were weighed in a molar ratio of 1:2.4:17.6 and ground in a mortar for 30 minutes to uniformly mix the materials, and the mixture was transferred to a nickel crucible and placed in a muffle furnace, and heated to 250°C at a heating rate of 4°C / min at room temperature in an air atmosphere, and then kept warm for 15 minutes, and then continued to heat to 280°C at a heating rate of 2°C / min and kept warm for 6 hours, and then naturally cooled to room temperature to obtain a calcined product;

[0079] 4) The calcined product was washed and filtered three times with deionized water and anhydrous ethanol respectively to remove excess lithium salt and sodium salt. The final clean material was transferred to a glass dish and dried in an oven for 24 hours to remove excess moisture to obtain Li2Mn3O7 material (600℃-15h). After fine grinding, it was sealed and dried for storage.

[0080] Example 5

[0081] A manganese-based material, the preparation method is as follows:

[0082] 1) Firstly, sodium carbonate and manganese carbonate powders were weighed in a molar ratio of 1:3 and put into a ball mill, and ball milled and mixed for 24 hours at a rotation speed of 400 rpm to obtain a mixture;

[0083] 2) The obtained mixture was spread in a square porcelain boat, placed in a tube furnace and oxygen was introduced, and heated to 450°C at a heating rate of 5°C / min and kept for 5 hours in a pure oxygen atmosphere and room temperature of 25°C, and then heated to 600°C at a heating rate of 3°C / min and kept for 18 hours, and then cooled naturally to room temperature while maintaining ventilation to obtain a Na2Mn3O7 precursor;

[0084] 3) Na2Mn3O7 precursor, lithium chloride and lithium nitrate were weighed in a molar ratio of 1:2.4:17.6 and ground in a mortar for 30 minutes to uniformly mix the materials, and the mixture was transferred to a nickel crucible and placed in a muffle furnace, and heated to 250°C at a heating rate of 4°C / min at room temperature in an air atmosphere, and then kept warm for 15 minutes, and then continued to heat to 280°C at a heating rate of 2°C / min and kept warm for 6 hours, and then naturally cooled to room temperature to obtain a calcined product;

[0085] 4) The calcined product was washed and filtered three times with deionized water and anhydrous ethanol respectively to remove excess lithium salt and sodium salt. The final clean material was transferred to a glass dish and dried in an oven for 24 hours to remove excess moisture to obtain Li2Mn3O7 material (600℃-18h). After fine grinding, it was sealed and dried for storage.

[0086] The precursor sintering temperatures of Examples 2, 4 and 5 are the same, all at 600°C. The difference is that the sintering holding time of the precursors is 12, 15 and 18h, respectively. The prepared materials are subjected to X-ray diffraction with a scanning range of 10 to 90°. The obtained XRD patterns are as follows: Figure 2 As shown in the figure, when the holding time is increased to 15h, the (003) peak of the material is the sharpest and the crystallinity is the best; when the holding time is extended to 18h, the (104) peak splits and the symmetry of the layered structure decreases. Therefore, the precursor has better structure and performance when the sintering temperature is 600℃ and the holding time is 15h.

[0087] Example 6

[0088] A manganese-based material, the preparation method is as follows:

[0089] 1) Firstly, sodium carbonate and manganese carbonate powders were weighed in a molar ratio of 1:3 and put into a ball mill, and ball milled and mixed for 24 hours at a rotation speed of 400 rpm to obtain a mixture;

[0090] 2) The obtained mixture was spread flat in a square porcelain boat, placed in a tube furnace and oxygen was introduced, and heated to 450°C at a heating rate of 5°C / min and kept for 5 hours in a pure oxygen atmosphere and room temperature of 25°C, and then heated to 600°C at a heating rate of 3°C / min and kept for 15 hours, and then cooled naturally to room temperature while maintaining ventilation to obtain a Na2Mn3O7 precursor;

[0091] 3) Na2Mn3O7 precursor, lithium chloride and lithium nitrate were weighed in a molar ratio of 1:2.4:17.6 and ground in a mortar for 30 minutes to uniformly mix the materials, and the mixture was transferred to a nickel crucible and placed in a muffle furnace. The mixture was heated to 250°C at a heating rate of 4°C / min in an air atmosphere at room temperature, and then kept warm for 15 minutes, and then continued to be heated to 280°C at a heating rate of 2°C / min and kept warm for 2 hours, and then naturally cooled to room temperature to obtain a calcined product;

[0092] 4) The calcined product was washed and filtered three times with deionized water and anhydrous ethanol respectively to remove excess lithium salt and sodium salt. The final clean material was transferred to a glass dish and dried in an oven for 24 hours to remove excess moisture to obtain Li2Mn3O7 material (600℃-15h-2h). After fine grinding, it was sealed and dried for storage.

[0093] Example 7

[0094] A manganese-based material, the preparation method is as follows:

[0095] 1) Firstly, sodium carbonate and manganese carbonate powders were weighed in a molar ratio of 1:3 and put into a ball mill, and ball milled and mixed for 24 hours at a rotation speed of 400 rpm to obtain a mixture;

[0096] 2) The obtained mixture was spread flat in a square porcelain boat, placed in a tube furnace and oxygen was introduced, and heated to 450°C at a heating rate of 5°C / min and kept for 5 hours in a pure oxygen atmosphere and room temperature of 25°C, and then heated to 600°C at a heating rate of 3°C / min and kept for 15 hours, and then cooled naturally to room temperature while maintaining ventilation to obtain a Na2Mn3O7 precursor;

[0097] 3) Na2Mn3O7 precursor, lithium chloride and lithium nitrate were weighed in a molar ratio of 1:2.4:17.6 and ground in a mortar for 30 minutes to uniformly mix the materials, and the mixture was transferred to a nickel crucible and placed in a muffle furnace, and heated to 250°C at a heating rate of 4°C / min at room temperature in an air atmosphere, and then kept warm for 15 minutes, and then continued to heat to 280°C at a heating rate of 2°C / min and kept warm for 10 hours, and then naturally cooled to room temperature to obtain a calcined product;

[0098] 4) The calcined product was washed and filtered three times with deionized water and anhydrous ethanol respectively to remove excess lithium salt and sodium salt. The final clean material was transferred to a glass dish and dried in an oven for 24 hours to remove excess moisture to obtain Li2Mn3O7 material (600℃-15h-10h). After fine grinding, it was sealed and dried for storage.

[0099] The difference between Examples 2, 6 and 7 is that the ion exchange time is 2h, 6h and 10h respectively. The prepared materials are subjected to X-ray diffraction with a scanning range of 10 to 90°. The obtained XRD patterns are as follows: Figure 3 As shown in the figure, the (003) main peak of the material with an ion exchange time of 10 hours is broadened, and some peaks in the range of 55-90° merge, which means that the material structure will have disordered stacking, lattice distortion, and reduced structural symmetry. From the XRD diffraction curves of ion exchange times of 2h and 6h, it can be seen that the ratio of I(003) / I(104) is larger when the exchange time is 6h, and the atomic arrangement is more orderly.

[0100] In summary, among Examples 1 to 7, the preparation conditions of the better Li2Mn3O7 sample are those of Example 4. The Li2Mn3O7 sample prepared in Example 4 is hereinafter referred to as P-LMO.

[0101] Example 8

[0102] A manganese-based material, which differs from Example 4 in that step 1) of this example is: sodium carbonate, manganese carbonate and lithium carbonate powder are weighed in a molar ratio of 1:3:0.045, and put into a ball mill, and ball milled for 24 hours to mix evenly at a speed of 400 rpm; other steps and raw materials are the same as those of Example 4. The sample obtained in this example is recorded as D-LMO-0.045.

[0103] Example 9

[0104] A manganese-based material, which differs from Example 4 in that step 1) of this example is: sodium carbonate, manganese carbonate and lithium carbonate powder are weighed in a molar ratio of 1:3:0.09, and put into a ball mill, and ball milled for 24 hours to mix evenly at a speed of 400 rpm; other steps and raw materials are the same as those of Example 4. The sample obtained in this example is recorded as D-LMO-0.09.

[0105] Example 10

[0106] A manganese-based material, which differs from Example 4 in that step 1) of this example is: sodium carbonate, manganese carbonate and lithium carbonate powder are weighed in a molar ratio of 1:3:0.14, and put into a ball mill, and ball milled for 24 hours to mix evenly at a speed of 400 rpm; other steps and raw materials are the same as those of Example 4. The sample obtained in this example is recorded as D-LMO-0.14.

[0107] Embodiment 11

[0108] A manganese-based material, which differs from Example 4 in that step 1) of this example is: sodium carbonate, manganese carbonate and lithium carbonate powder are weighed in a molar ratio of 1:3:0.24, and put into a ball mill, and ball milled for 24 hours to mix evenly at a speed of 400 rpm; other steps and raw materials are the same as those of Example 4. The sample obtained in this example is recorded as D-LMO-0.24.

[0109] The four samples obtained in Examples 8 to 11 were confirmed by X-ray diffraction, with a scanning range of 10 to 90°. The obtained XRD patterns are as follows: Figure 4As shown. It can be seen that the positions and patterns of the superlattice diffraction peaks of the four lithium-doped samples in the range of 22 to 28° have changed. It may be that the addition of additional lithium has changed the arrangement order of Mn vacancies in the material. Compared with P-LMO, the (104) peak of the lithium-doped samples of D-LMO-0.045, D-LMO-0.09, and D-LMO-0.24 has a shoulder peak or a blunt peak shape, and the peak is broadened and widened, which means that the structural symmetry of the crystal and the ordered distribution of the spatial superstructure of the three lithium-doped modified samples are reduced to varying degrees. The crystal form of the D-LMO-0.14 sample is complete, and the superstructure diffraction peak moves to a lower angle relative to the original sample as a whole, which means that the occupation of lithium in the Mn vacancy leads to a reduction in the proportion of Mn vacancies and re-arrangement, and the distribution of the Mn vacancy structure will be more dispersed.

[0110] The preparation conditions of the solid sintering process and the ion exchange process of the NaLiMnO (NLMO) precursor obtained in Examples 8 to 11 are consistent with the optimal preparation conditions of LMO in Examples 1 to 7.

[0111] In summary, among Examples 8 to 11, the better lithium doping strategy is Example 10. The lithium-doped Li2Mn3O7 sample prepared in Example 10 is hereinafter referred to as D-LMO.

[0112] The morphology of the samples of Example 4 (P-LMO) and Example 10 (D-LMO) was observed by scanning electron microscopy. The SEM images are as follows: Figure 5 As shown, (a) is P-LMO and (b) is D-LMO. Figure 5 (a)) is an irregular single crystal particle with a size of about 200 to 400 nm. The nano-crystal material is more conducive to the rapid insertion and extraction of lithium ions, and can provide good rate performance in the actual application of lithium-ion batteries. Figure 5 (b)), the morphology has no obvious change compared with P-LMO, and the particle surface is smooth and free of foreign matter.

[0113] EDS spectrum test was performed on the two samples, and the results are as follows: Figures 6-7 As shown, Figure 6 is the EDS element spectrum of the sample in Example 4, Figure 7 The EDS element spectrum of the sample of Example 10 shows that the manganese element of the two samples is evenly distributed, and a small amount of sodium remains on the surface of the sample. Through further ICP element analysis test, the ICP test results are shown in Table 1. It can be seen that the sodium content is very small, and the ion exchange reaction can be considered complete. The molecular formula of the material P-LMO actually obtained is Li 0.64 [□ 0.14 Mn 0.86]O2, the molecular formula of D-LMO is Li 0.64 [Li 0.11 □ 0.03 Mn 0.86 ]O2; the actual chemical composition of the above two materials and the target chemical composition Li 0.57 [□ 0.14 Mn 0.86 ]O2、Li 0.64 [Li 0.09 □ 0.05 Mn 0.86 ]O2 results are very close, and it can be considered that the target product has been obtained.

[0114] Table 1 ICP test results of P-LMO and D-LMO

[0115] P-LMO Mass percentage (%) Molar Ratio D-LMO Mass percentage (%) Molar Ratio Li 5.0435 0.7541 Li 6.0803 0.8761 Na 0.1604 0.0072 Na 0.0527 0.0023 Mn 52.9696 1 Mn 54.6763 1

[0116] The manganese-based materials of Example 4 and Example 10 were made into pole pieces, and half-cells were assembled for electrochemical testing. The specific steps are as follows:

[0117] Weigh the P-LMO and D-LMO positive electrode materials with polyvinylidene fluoride PVDF and conductive carbon black in a ratio of 8:1:1, add an appropriate amount of N-methylpyrrolidone solvent NMP and grind evenly, and coat it on aluminum foil with a 200μm thick scraper, dry it at 60℃ and then vacuum dry it at 100℃ for 10h, take it out and cut it into a 12mm diameter disc, use it as the positive electrode, lithium metal as the negative electrode, glass fiber as the separator, and 1.2M LiPF6, EC:EMC=3:7Vol% as the electrolyte to assemble it into a 2032 button half-cell for electrochemical testing. The test results are as follows: Figure 8 As shown, (a) is a long cycle performance test diagram of a battery assembled by D-LMO and P-LMO, which is activated for 5 cycles at 2-4.8V and 0.1C current and performed at 0.2C current; (b) is the charge and discharge curve of the battery assembled by P-LMO in the first two cycles; (c) is the charge and discharge curve of the battery assembled by D-LMO in the first two cycles.

[0118] like Figure 8(a), the discharge capacity of the P-LMO assembled battery is 241mAh / g after five cycles of low current activation, and the first cycle shows a discharge capacity of 230mAh / g under 0.2C current. After 100 cycles, the discharge capacity is 190mAh / g, and the capacity retention rate is 82.6%; in contrast, the discharge capacity of D-LMO is 251.42mAh / g after five cycles of 0.1C current activation, and there is still a capacity of 243mAh / g after 100 cycles of 0.2C. It can be seen that the addition of Li greatly improves the material cycle stability and cycle life, and also improves the actual capacity of the material. The reason is that Li doping will occupy some Mn vacancies, which will cause the arrangement order of Mn atoms in the transition metal layer to change. Combined with the phenomenon that the superlattice diffraction peak in the XRD graph shifts to a low angle, it can be known that the mesh vacancy distribution structure in the original material will be rearranged in D-LMO, and the vacancy arrangement is more dispersed. This results in a higher barrier for Mn migration in the transition metal layer, making it more difficult for adjacent peroxides around the vacancies to combine to form oxygen. The intra-layer / inter-layer migration of manganese is suppressed, which is more conducive to maintaining the stability of the material structure and reversible capacity release. Figure 8 (b) to (c), comparing the charge and discharge curves of the first two cycles of P-LMO and D-LMO, it can be seen that the first cycle charge capacity of the sample P-LMO is 54mAh / g, and the Li-doped material D-LMO has a significant improvement, showing a first cycle charge capacity of 94mAh / g. The higher capacity is reflected in the reaction of the 4.6V high voltage platform, which is believed to be due to the occupation of Li on the Mn vacancy to activate more lattice oxygen to participate in the redox reaction. The occupation of additional Li on the Mn vacancy in the transition metal layer will cause the classic "Li-O-Li" configuration to appear in the material. In many lithium-rich manganese materials, it is the source of additional capacity for activating lattice oxygen redox. However, in traditional lithium-rich materials, lattice oxygen is easily irreversibly oxidized to oxygen during the first cycle of charge and discharge, and the high-voltage reaction platform disappears in the second cycle, resulting in serious loss of capacity in the first cycle. In the materials of this patent, it is clearly found that the first cycle irreversible capacity loss of the two materials is extremely small, and the high-voltage reaction platform can be reproduced in the second cycle, proving that the irreversible reaction of lattice oxygen is suppressed, thanks to the application of the Mn vacancy structure.

[0119] For the layered all-manganese-based lithium ion cathode oxide with a specific Mn vacancy structure of the transition metal layer (such as a mesh structure) synthesized in the embodiment of the present invention, it is difficult to synthesize it by the traditional solid phase sintering method due to the particularity of its atomic arrangement. The embodiment of the present invention fills this technical gap by using the ion exchange method, and prepares a new type of lithium ion cathode oxide material with a Mn vacancy structure. From the XRD test results, the superlattice structure of the transition metal layer of the sodium precursor is retained, and it exhibits ultra-high capacity during the lithium ion battery test. In Examples 1 to 7 of the present invention, the optimal preparation conditions of the precursor Na2Mn3O7 are determined (sodium carbonate and manganese carbonate are used as precursor preparation materials, oxygen atmosphere, high temperature 600°C insulation for 15 hours), and the optimal preparation conditions of ion exchange are determined (lithium chloride and lithium nitrate are used as lithium salts, the mixing ratio of the two salts is 12:88, and the ion exchange is carried out at 280°C for 6 hours). In Examples 8 to 11 of this case, the original material Li2Mn3O7 (Li 0.57 [□ 0.14 Mn 0.86 ]O2) is modified by in-situ lithium supplementation, and the Mn vacancies in the transition metal layer are partially occupied by Li. The doped lithium source is anhydrous lithium carbonate, and the additional lithium atoms account for 63% of the Mn vacancies. The manganese-based materials prepared in Examples 1 to 11 of the present invention are assembled into half-cells, showing good electrochemical performance.

[0120] In summary, in the manganese-based material with a specific structure of the present invention, the unique Mn vacancies in the transition metal layer can activate the redox activity of oxygen anions, provide additional capacity during the charge and discharge process, and enrich the existing crystal structure configuration of this material; further, the structure is reversely designed according to the characteristics of lithium deficiency in the material, and lithium is supplemented in situ to optimize the application of this structure in lithium-ion batteries. The addition of additional lithium atoms will lead to the rearrangement of the Mn vacancy superstructure in the transition metal layer, and the more dispersed vacancy configuration can better inhibit the irreversible loss of lattice oxygen and the structural phase change and capacity loss caused by migration within / between the manganese layer.

Claims

1. A manganese-based material, characterized in that: The crystal structure of the manganese-based material includes an alkali metal layer, an O element and a transition metal layer; the O element is located between the alkali metal layer and the transition metal layer, and is respectively combined with the alkali metal layer and the transition metal layer; the alkali metal layer includes a Li element; the transition metal layer includes a Mn element and a Mn vacancy, or a Mn element, a Mn vacancy and a Li element; The molar ratio of the O element to the Li element in the alkali metal layer is 1:(0.2-0.4); The molar ratio of the O element to the Mn element is 1:(0.3-0.6); The molar ratio of the Mn vacancy to the Mn element is greater than 0 and less than or equal to 1 / 6; The molar ratio of the Li element to the Mn element in the transition metal layer is 0 to 0.

16.

2. The manganese-based material according to claim 1, characterized in that: The crystal structure of the manganese-based material includes an O2 phase structure, an O3 phase structure or a combination thereof.

3. The manganese-based material according to claim 1, characterized in that: The transition metal layer includes Mn element, Mn vacancies and Li element; the molar ratio of Li element to Mn element in the transition metal layer is greater than 0 and less than or equal to 0.

16.

4. A method for preparing a manganese-based material according to any one of claims 1 to 3, characterized in that: The following steps are involved: A mixture containing sodium carbonate and manganese carbonate, or a mixture containing sodium carbonate, manganese carbonate and a first lithium source, is calcined for the first time to obtain a precursor; the precursor is then mixed with a second lithium source, and an ion exchange reaction is performed through a second calcination to obtain the manganese-based material; the first lithium source and the second lithium source are the same or different.

5. The preparation method according to claim 4, characterized in that: The calcination temperature of the first calcination is 500-700°C; And / or, the holding time of the first calcination is 12 to 18 hours.

6. The preparation method according to claim 4, characterized in that: The calcination temperature of the second calcination is 200-300°C; And / or, the second calcination is carried out for a holding time of 2 to 10 hours.

7. The preparation method according to claim 4, characterized in that: The first lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium chloride or lithium nitrate; And / or, the second lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium chloride or lithium nitrate.

8. The preparation method according to claim 7, characterized in that: The first lithium source is selected from lithium carbonate; And / or, the second lithium source is selected from lithium chloride and lithium nitrate; the mass ratio of the lithium chloride to the lithium nitrate is 1:(7-8).

9. A positive electrode material, characterized in that: The raw material for preparing the positive electrode material includes the manganese-based material described in any one of claims 1 to 3, or the manganese-based material prepared by the preparation method described in any one of claims 4 to 8.

10. A lithium ion battery, characterized in that: Comprising the positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Secondary battery electrode material containing intrinsic vacancy and battery

    CN109616648A

  • Manganese vacancy regulation and control lithium-rich manganese-based positive electrode material modification method and application of material

    CN114678522A

  • Synthesis method of low-voltage hysteresis O2 type lithium-rich manganese-based positive electrode material

    CN114695874A

  • Manganese-based layered positive electrode material for high-specific-energy sodium-ion battery, and preparation method and application of manganese-based layered positive electrode material

    CN115117336A

  • Metastable-phase lithium-rich manganese-based positive electrode material, preparation method thereof and lithium ion battery

    CN116443940A